Ground response analysis in offshore Terengganu - Mohamad, M. (Construction Research Institute of Malaysia, 2020)
The amount of vibration experienced by any specific location with respect to bedrock in any seismic event can be predicted using a ground motion equation. Results from this analysis are important as it will be used in the design process of engineering structure to withstand a horizontal load from a seismic event. However, by depending on these values, the possibility of amplification or de-amplification of acceleration under the local soil effect has been ignored. The occurrence of amplification will result in higher acceleration on the surface and produce higher lateral load to fixed platforms in offshore Terengganu. These platforms have been designed without provision to seismic load. Therefore, this study focuses on ground response analysis in offshore Terengganu. Four sites have been selected where all sites are considered as stiff soil. Related input data has been extracted from the soil investigation report and Nias-Simeulue earthquake was used as earthquake profile. Four developed correlation equations have been adopted in determining shear wave velocity. One dimensional nonlinear ground response analysis program, namely NERA has been used to analyse local site effect. Peak surface acceleration in each site has been obtained. Results show that the occurrence of soil amplification ranging from 1.6 to 2.0 in the study areas. Â© 2020, Construction Research Institute of Malaysia. All rights reserved.